Соёл хоорондын чадамж гадаад хэлний хичээлийн зорилго болох нь (МУИС-ийн мэргэжлийн ангийн гадаад хэлний багш нараас авсан түүвэр судалгаа): Intercultural competence - a goal of foreign language teaching (Survey outcomes based on data of some teachers for study courses in foreign language at the NUM) - Ch., Selengemurun (Mongolian Journal of Foreign Languages and Cultures, 2023)
In this article will be discussed the intercultural competence which must be acquired by foreign language learning. The definition and different models of intercultural competence and their contents will be shown for the demonstration that the intercultural competence is not an unknown term. This is a part of the skills in reading, writing, listening and speaking of foreign language teaching and learning, particularly a part of communicative and action competence which are known for teachers already. A survey was inquired for demonstrating the engagement by foreign language teachers to teach their learners in intercultural competence; the outcomes were analyzed by SPSS 23 statistic program within this article.